Peran Audit Dalam Pengendalian Internal Serta Pengungkapan Kerugian Material Untuk Good Corporate Governance - I Wayan Sukariana; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2015)
The aim of this study is 1) To determine the influence of the competence of internalauditors on the disclosure of material losses Regional Development Bank (BPD) Bali, 2) Todetermine the influence of the objectivity of the internal auditors on the disclosure of materiallosses Regional Development Bank (BPD) Bali, 3) To determine the effect investment SDMon internal auditors to the disclosure of material losses Regional Development Bank (BPD)Bali, 4) To determine the effect Disclosure Losses Material for GCG (GCG) RegionalDevelopment Bank (BPD) Bali, 5) To determine the effect of Competence for GCG (GoodCorporate Governance) Regional Development Bank (BPD) Bali, 6) To determine theinfluence of objectivity to the GCG (GCG) Regional Development Bank (BPD) Bali, 7) Todetermine the influence of HRD investment to GCG (GCG) Regional Development Bank(BPD) Bali.The study found the effect of variable competence on the disclosure of material lossesare significant, 2) Effect of variable objectivity on the disclosure of material losses aresignificant, 3) Effect of investment variables HR on the disclosure of material losses aresignificant, 4) Effect of variable competence against the interest of good corporategovernance is a significant , 5) Effect of variable objectivity towards good corporategovernance are significant, 6) Effect of variable human resource investment to goodcorporate governance are significant, 7) Effect of variable the influence of HRD investment issignificant.Keywords: competence, objectivity, HR investments, the disclosure of material losses, andgood corporate governance